Lie. čiùtnas „dailus, švarus, tvarkingas…“, taũsti (-čia) „ilgėtis, liūdėti“ ir jų giminaičiai - Karaliūnas, Simas (Baltistica, 1976)
LITH. čiùtnas “CLEAN, NEAT, TIDY…”, taũsti (-čia) “TO LONG, TO BE SAD, TO GRIEVE” AND THEIR COGNATES The author argues in the paper that the lexemes čiùtnas, čiutnùs “clean, neat, tidy; frisky, agile, swift”, čiutlùs “clean, neat, tidy”, čiutė́ti (čiùta) “lie in bed, drowse, slumber”, čiūtė́ti (čiū̃ti) “sit, lie motionlessly, hide”, čiūtinti “look after carefully, spoil”, tùtinti “spoil (by too much tenderness)”, tuténti “look after (a patient); wrap up, envelop, dress”, tautė́ti (-ė́ja) “look after, take care”, taũsti (-čia) “long, be sad, grieve”, (-sta) “grow thin, weaker, feeble, be hard-up, be in distress, want; faint, swoon, be dizzy”, nu-taũsti (-sta, -čia) “forget one’s family, home, break oneself of relatives, fall out, shim”, tautà “gens, nation” (and its correspondings in other IE languages), čiū́tys “a large number”, čiū̃tė “cone”, tūta “work, misery”, Latv. tũte “energy, power, strength”, tūtars “a small heap, pile of corn, hayrick, haystack”, tutinât “wrap up, envelop, dress” etc. might be cognate and belong to the IE root *teu̯(ǝ) – “swell, distend”.